Tradition Mulao Cucu Ayae After Marriage Contract in Sungai Liuk Village: Urf and Interactionism Approach - Mayang Sari, Marsika; Zufriani, Zufriani; Iskandar, Nuzul (Alhurriyah, 2024)
The Mulao Cucu Ayae Tradition is a significant ceremony in Sungai Liuk Village, Kerinci, performed after the marriage contract. This study explores the symbolic meaning of the tradition and its role in fostering social and religious values. Using a qualitative descriptive approach, data were gathered through interviews and observations with local traditional leaders. The findings reveal that Mulao Cucu Ayae serves as both a religious ritual and a moral guide, instilling discipline and cleanliness in the prospective couple's household. Key symbols, such as "banana dandan kelapa," play a role in enhancing personal growth and community identity. Additionally, the tradition strengthens cultural ties and interpersonal relationships within the local community. This research underscores the importance of preserving such ceremonies and contributes to a broader understanding of Indonesia's rich and diverse religious traditions.